Pain during medical abortion: a multicenter study in France. (November 2015) - Saurel-Cubizolles, Marie-Josèphe; Opatowski, Marion; David, Philippe; Bardy, Françoise; Dunbavand, Annabel
Abstract: Objective: To compare the level of pain reported by women by dose of mifepristone, 200 or 600 mg, and describe the main factors related to the pain level in the 5 days after a medical abortion. Study design: Observational study in 11 medical centers in France between October 2013 and September 2014. The protocols were 200 or 600 mg orally mifepristone on day 1 of the medical abortion and 400, 600 or 800 μg orally misoprostol on day 3. Women returned a questionnaire that they completed during 5 days following the abortion; pain was recorded on a visual analog scale (0–10) daily. Results: 453 women were included; the mean age was 29 years (range 18–49 years). Pain was greater with 200 than 600 mg mifepristone: 33% of women reported a pain level of ≥8 on day 3 with 200 mg as compared with 16% with 600 mg. This difference remained after controlling for age, gestational age, gravidity, usual painful menstruation and misoprostol dose. Percentages of symptoms as vomiting or diarrhea were also lower with 600 mg mifépristone than 200 mg. Conclusion: The mean pain severity experienced by women undergoing medical abortion is high; it is higher with a regimen of 200 mg mifepristone. The findings emphasize the need to improve analgesic strategies and invite to opt for a protocol of 600 mg instead of 200 mg mifepristone.